PERANCANGAN APLIKASI KOPERASI SYARIAH SIMPAN PINJAM BERBASIS WEB (STUDI KASUS KOPERASI BMT DARUL MUTTAQIEN) - Auzan Muhammad Yustanto; Sri Mulyati (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Abstract− Baitul Maal Tamwil (BMT) is an institution consisting of two terms, namely baitul maal and baitul tamwil. This institution was established with the intention of facilitating the lower communities that are not reached by the services of Islamic banks or Islamic BPRs. The operational principles used are the principles of profit sharing, buying and selling and entrustment. Therefore, although it is similar to the Islamic bank BMT has its own market, namely a small community. It's just that what distinguishes sharia cooperatives from other cooperatives is the operational system. The sharia system in sharia cooperatives does not allow usury or in its default language it is called "interest". The interest system in Sharia cooperatives is replaced by a profit-sharing system, in addition, everything that smells of gambling or unproductive speculation and unclear transactions is also forbidden to be practiced in this type of cooperative. BMT Darul Muttaqien Savings and Loans Cooperative located on Jl, Raya Jakarta Bogor KM. 41, Jabon Mekar, Parung District, Bogor. is a sharia microfinance institution engaged in raising and distributing funds to develop the community's economy that runs operations based on Islamic law (sharia). The system running on the BMT Darul Muttaqien Savings and Loan Cooperative currently applies as a new member still by filling out the registration form and must get approval from the chairman of the cooperative. The new member registration application form is collected in advance at the admin while waiting for other registrants, a minimum of 4-5 people. It takes time and is prone to being tucked away/lost. Furthermore, to deposit money (save), the applicant must fill out a money deposit form and submit it back to the admin staff The money deposit process is still through the form and it is necessary to know the chairman of the cooperativeFrom the above problems, BMT Darul Muttaqien Savings and Loans requires a savings and loans application to assist in the process of systematic member registration, recording, or management of all integrated transactions to make it easier to make reports. There are several reports including member loan reports, member deposit reports, member bill statements, member loan due reports, and results reports for members. and results reports for members. And there is a reminder for members who are stuck paying installments. Will be recorded on a web-based application. Based on the problems that exist in the BMT Savings and Loans Cooperative darul Muttaqien, a study was conducted with the title “PERANCANGAN APLIKASI KOPERASI SYARIAH SIMPAN PINJAM BERBASIS WEB (STUDI KASUS KOPERASI BMT DARUL MUTTAQIEN)”.